Dental students' knowledge and practices regarding disinfection and sterilization of extracted human teeth - Omar, Ola Moustafa; Farrag, Nadia Mostafa (International Journal of Infection Control, 2016)
Extracted human teeth are used by dental students in preclinical courses to practice on them different dental procedures, however they can be a source of infection. According to Center for disease control, extracted teeth should be disinfected or sterilized before use. The current study aimed to assess knowledge and practices regarding disinfection and sterilization of extracted human teeth in a group of dental students.This descriptive cross-sectional study was carried out on third, fourth and fifth- year dental students at College of Dentistry, Taibah University, Saudi Arabia. A self-administered questionnaire was prepared based on a previous study which tests the knowledge and practice of students regarding disinfection and sterilization of extracted human teeth. Results of this study showed that most of the students in all grades agreed that it is necessary to disinfect and/or sterilize extracted teeth before working on them. They reported also that it is mandatory to use specific precautions while working in these teeth since they can be a source of infection and there is a chance of disease transmission through them. The year of education affected the response, where 92.5% of fourth grade students agreed that there is a necessity to disinfect and/or sterilize extracted teeth before working on them in comparison to third grade students who recorded the lowest score (70.4%) with statistically significant difference. Hydrogen peroxide, sodium hypochlorite and autoclaving got the highest scores for teeth sterilization and/or disinfection among the three different grades with insignificant statistical difference. Regarding the practices of students no statistical significant difference was found between the three grades regarding the sterilization methods for extracted teeth and their use of protective barriers during handling of them. Most of students reported that their source of knowledge was taught in dental courses or from instructions from dental staff members with no statistical significant differences between the grades or gender. The results of the present study concluded that knowledge and practices of dental students at Taibah University in relation to sterilization/disinfection methods of extracted human teeth was satisfactory.